LEGAL CONSEQUENCES OF IMPLEMENTATION BUSINESS PARTNER AGREEMENTS USING THE CONCEPT OF FRENCHISE DRINK JERUKI - Sunaryo Sunaryo; Rissa Afni Martinouva Rissa (Law Faculty of Universitas Bandar Lampung, 2023)
Franchising is a special right that is owned by an individual or business entity against a business system with business characteristics. This concept has proven successful and can be used by other parties based on a franchise agreement. The Jeruki beverage business cooperation has criteria and business characteristics that have similarities with the franchise agreement, system, concept and model. This citrus drink business which has a concept like a franchise already has 15 (fifteen business partners). The implementation of a franchise business is guided by a franchise agreement that must be made in writing between the franchisor and the franchisee. The Jeruki beverage company has a big chance to get a place as a franchise. This invites an analysis of whether the constraints of the citrus drink business have not been realized as a franchise and what are the legal consequences. The cooperation agreement is in the form of a franchise, however, to be said to be a business with a franchise concept, it must comply with the franchise agreement clause in accordance with the Regulation of the Minister of Trade Number 12 of 2006 concerning Provisions and Procedures for Issuing a Franchise Business Certificate and Regulation of the Minister of Trade Number 71 of 2019 concerning the Implementation of a Franchise . Unregistered trademarks and a lack of understanding of the concept of franchising cause huge losses to the initial owners of the business. The act of imitating the business concept of drinking oranges by other parties is very difficult to stop because the brand has not been registered.